6k-13=4k+14

Simple and best practice solution for 6k-13=4k+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6k-13=4k+14 equation:


Simplifying
6k + -13 = 4k + 14

Reorder the terms:
-13 + 6k = 4k + 14

Reorder the terms:
-13 + 6k = 14 + 4k

Solving
-13 + 6k = 14 + 4k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-4k' to each side of the equation.
-13 + 6k + -4k = 14 + 4k + -4k

Combine like terms: 6k + -4k = 2k
-13 + 2k = 14 + 4k + -4k

Combine like terms: 4k + -4k = 0
-13 + 2k = 14 + 0
-13 + 2k = 14

Add '13' to each side of the equation.
-13 + 13 + 2k = 14 + 13

Combine like terms: -13 + 13 = 0
0 + 2k = 14 + 13
2k = 14 + 13

Combine like terms: 14 + 13 = 27
2k = 27

Divide each side by '2'.
k = 13.5

Simplifying
k = 13.5

See similar equations:

| x/3+5=x/6+18 | | -32-16-(-27)= | | -4(-3a+6)+8(8a+7)=-44 | | 2+3x+5=25 | | 3x+2x+7=22 | | 2z^2+2z+13=0 | | (295.5-y)/5.5=x | | 3(8-7n)=-34+8n | | 295.50-y/5.5=x | | m-3=2 | | -56+38= | | -7*-7+6y=-42 | | 4a-8(-5-6a)=40-8a | | 11+3x-7=9 | | 106=-7(p-7)+1 | | -1=-10/9x+10 | | -1=-10/9+10 | | -16-5x=5-sx | | (4x-3)/5=(2x-7)/8 | | -1.1111=-10/9x+10 | | -1.1111=-10/9+10 | | 82=4x-2(1-4x) | | -10/9*-1.1111+10 | | 4/3*6.4615-8=y | | -1/2*-5 | | -x/2+5=-1 | | x/4-2=-7 | | 4(3g-5)=52 | | 2x-1=z+2 | | (4/3x)-8=(-8/7x)+8 | | 4/3-8=-8/-7+8 | | 4/3x-8=-8/7+8 |

Equations solver categories